KONSTRUKSI MEDIA TERHADAP STEREOTIPE GENDER:ANALISIS FRAMING TERHADAP KASUS PEMERKOSAAN DI MEDIA CETAKAli Imron Fakultas Ilmu Sosial, Universitas Negeri Surabaya (Lentera, Jurnal Studi Perempuan, 2013)
AbstractThe construction of mass media that like to dramatize and blow up the news about rape, make the victims harm and bring gender bias. This writing analyzed the rape reports in mass media using Framing analysis. The result shows that mass media is not only report the rape event, but also expose the victim identity and the visual image. This report is believed as a way to show the truth and fact. However, it is also obscure the factual and fictional reality that promote different interpretation from the readers.Keywords: patriarchy, gender, rape, Framing analysis